Quince cultivars selection to tropical regions - Coutinho, Givago (2017)
The quince tree is a temperate climate fruit crop of a historical importance in the development of some regions of Brazil. However, with the passing of times, its cultivation declined, culminating in the extinction of almost all Brazilian quince tree crops. Nowadays, the quince tree culture is going through a moment of transition, with the perspective of revitalization of the national production. Starting from this principle, the first work had the objective of identifying quince tree cultivars using a multivariate analysis and genetic divergence in the process of evaluation of phenotypic characters related to plant phenology that are promising for cultivation in the tropics. To quantify the divergence between the cultivars, the genetic distance was used, based on the Gower algorithm, the UPGMA clustering method, the multivariate clustering and main components analysis. The group that includes the cultivars ‘Alaranjado’, ‘Lajeado’, ‘Portugal’, ‘CTS 207’, ‘Provence’ and ‘Bereckzy’, stood out from the other groups for presenting better results in the variables that obtained the greatest contribution in the PCA. The characteristics of the number of buds per branch and brindles per branch contribute to the maximum variability in quince tree cultivars. The UPGMA group indicated the existence of genetic variability among the cultivars and present groups with more dissimilar accessions with potential to be used in future stages of quince selection. The cultivars ‘CTS 207’ and ‘Japonês’ have a high degree of genetic divergence among them in relation to the phenotypic characteristics studied. The second work had as objective to select cultivars of quince tree with better performance through indexes of selection for the cultivation in the tropics. Twenty-eight cultivars arranged in randomized blocks were used in three productive cycles. The phenotypic characteristics evaluated were: yield, harvest duration, duration of flowering, number of brindles per branch, and chilling hours. In the analysis of the obtained data, the rankings of the cultivars were based on the selection indexes: productivity, rank sum index and sum index of the standard variables. Subsequently, the coincidences and the correlation study between the indices evaluated were obtained. The cultivar 'Bereckzy' stood out for cultivation in the tropics, ranking first in the three indices studied. The highest correlation was obtained between Z index and sum of rankings, which shows the high relation between these selection indices in the evaluation of phenotypic characteristics of quince trees. The third work had the objective to characterize and evaluate the influence of different quince cultivars (‘Fuller’, ‘Smyrna’, ‘Portugal’, ‘Provence’, ‘Mendonza Inta-37’, ‘Alaranjado’, ‘Lajeado’, ‘Dangers’ and ‘Bereckzy’) cultivated in tropical regions of Brazil on the physical-chemical characteristics, rheological properties and sensory acceptance of marmalade in order to identify the cultivars with the greatest potential for industrial use. It was verified in this study that the different quince tree cultivars present great variability among themselves in relation to physical-chemical characteristics and in relation to the content of bioactive compounds and antioxidant activity. However, the study shown that the cultivars present similar marmalades between each other, which had a high sensory acceptance, except for the cultivar ‘Mendonza Inta-37’, which resulted in a less accepted marmalade. It can be concluded that quince tree cultivars cultivated in tropical regions present great processing potential in the form of marmalade.